Implementation of an Enhanced Recovery Protocol Is Associated With On-Time Initiation of Adjuvant Chemotherapy in Colorectal Cancer. Issue 11 (November 2019) - Hassinger, Taryn E.; Mehaffey, J. Hunter; Martin, Allison N.; Bauer-Nilsen, Kristine; Turrentine, Florence E.; Thiele, Robert H.; Sarosiek, Bethany M.; Reilley, Matthew J.; Hoang, Sook C.; Friel, Charles M.; Hedrick, Traci L.
Abstract : BACKGROUND: Delayed initiation of adjuvant chemotherapy negatively impacts long-term survival in patients with colorectal cancer. Colorectal enhanced recovery protocols result in decreased complications and length of stay; however, the impact of enhanced recovery on the timing of adjuvant chemotherapy remains unknown. OBJECTIVE: This study aimed to identify factors associated with on-time delivery of adjuvant chemotherapy after colorectal cancer surgery, hypothesizing that implementation of an enhanced recovery protocol would result in more patients receiving on-time chemotherapy. DESIGN: This was a retrospective cohort study comparing the rate of on-time adjuvant chemotherapy delivery after colorectal cancer resection before and after implementation of an enhanced recovery protocol. SETTINGS: The study was conducted at a large academic medical center. PATIENTS: All of the patients who underwent nonemergent colorectal cancer resections for curative intent from January 2010 to June 2017, excluding patients who had no indication for adjuvant chemotherapy, had received preoperative systemic chemotherapy, or did not have medical oncology records available were included. MAIN OUTCOME MEASURES: Patients before and enhanced recovery were compared, with the rate of on-time adjuvant chemotherapy delivery as the primary outcome. Adjuvant chemotherapy delivery was considered on time if initiated ⩽8 weeks postoperatively, and treatment was considered delayed or omitted if initiated >8 weeks postoperatively (delayed) or never received (omitted). Multivariable logistic regression identified predictors of on-time chemotherapy delivery. RESULTS: A total of 363 patients met inclusion criteria, with 189 patients (52.1%) undergoing surgery after enhanced recovery implementation. Groups differed in laparoscopic approach and median procedure duration, both of which were higher after enhanced recovery. Significantly more patients received on-time chemotherapy after enhanced recovery implementation ( p = 0.007). Enhanced recovery was an independent predictor of on-time adjuvant chemotherapy ( p = 0.014). LIMITATIONS: The study was limited by its retrospective and nonrandomized before-and-after design. CONCLUSIONS: Enhanced recovery was associated with receiving on-time adjuvant chemotherapy. As prompt initiation of adjuvant chemotherapy improves survival in colorectal cancer, future investigation of long-term oncologic outcomes is necessary to evaluate the potential impact of enhanced recovery on survival. See Video Abstract at http://links.lww.com/DCR/B21 . LA IMPLEMENTACIÓN DE UN PROTOCOLO DE RECUPERACIÓN ACELERADA SE ASOCIA CON EL INICIO A TIEMPO DE QUIMIOTERAPIA ADYUVANTE EN CÁNCER COLORRECTAL: ANTECEDENTES: El inicio tardío de la quimioterapia adyuvante afecta negativamente la supervivencia a largo plazo en pacientes con cáncer colorrectal. Los protocolos de recuperación acelerada colorrectales dan lugar a una disminución de las complicaciones y la duración de estancia hospitalaria; sin embargo, el impacto de la recuperación acelerada en el momento de inicio de quimioterapia adyuvante sigue siendo desconocido. OBJETIVO: Este estudio tuvo como objetivo identificar los factores asociados con la administración a tiempo de la quimioterapia adyuvante después de la cirugía de cáncer colorrectal, con la hipótesis de que la implementación de un protocolo de recuperación acelerada daría lugar a que más pacientes reciban quimioterapia a tiempo. DISEÑO: Estudio de cohorte retrospectivo que compara la tasa de administración de quimioterapia adyuvante a tiempo después de la resección del cáncer colorrectal antes y después de la implementación de un protocolo de recuperación acelerada. ESCENARIO: Centro médico académico grande. PACIENTES: Todos los pacientes que se sometieron a resecciones de cáncer colorrectal no emergentes con intención curativa desde enero de 2010 hasta junio de 2017, excluyendo a los pacientes que no tenían indicación de quimioterapia adyuvante, que recibieron quimioterapia sistémica preoperatoria o no tenían registros médicos de oncología disponibles. PRINCIPALES MEDIDAS DE RESULTADOS: Los pacientes se compararon antes y después de la implementación de la recuperación acelerada, con la tasa de administración de quimioterapia adyuvante a tiempo como el resultado primario. La administración de quimioterapia adyuvante se consideró a tiempo si se inició ⩽8 semanas después de la operación, y el tratamiento se consideró retrasado / omitido si se inició> 8 semanas después de la operación (retrasado) o nunca fue recibido (omitido). La regresión logística multivariable identificó predictores de administración de quimioterapia a tiempo. RESULTADOS: 363 pacientes cumplieron con los criterios de inclusión, con 189 (52.1%) pacientes sometidos a cirugía después de la implementación de recuperación acelerada. Los grupos difirieron en el abordaje laparoscópico y la duración media del procedimiento; ambos factores fueron mayores después de la recuperación acelerada. Significativamente más pacientes recibieron quimioterapia a tiempo después de la implementación de recuperación acelerada (p = 0.007). La recuperación acelerada fue un factor predictivo independiente de quimioterapia adyuvante a tiempo (p = 0.014). LIMITACIONES: Diseño retrospectivo, tipo ¨antes y después¨ no aleatorizado. CONCLUSIONES: La recuperación acelerada se asoció con la recepción de quimioterapia adyuvante a tiempo. Debido a que el inicio rápido de la quimioterapia adyuvante mejora la supervivencia en el cáncer colorrectal, en el futuro será necesario investigar los resultados oncológicos a largo plazo para evaluar el impacto potencial de la recuperación acelerada en la supervivencia. Vea el Resumen en Video en http://links.lww.com/DCR/B21 . Abstract : Supplemental Digital Content is available in the text.